HIERARKI MORFOLOGI PADA VERBA REDUPLIKASI BAHASA INDONESIA: Tinjauan dari Perspektif Morfologi Derivasi dan Infleksi - . Ermanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This reasearch studies the hirarchy of morphology in Indonesian particularly on the reduplication verb from derivational and inflectional morphology perspectives. It is a qualitative research applying structural linguistic method and making use of case grammar for semantic analysis. The result indicates that reduplication verb in Indonesia has four morphology hirarchical patterns which includes (1) (D + derivation reduplication) + inflectional affix (voice); (2) D + (reduplication + affix (derivation proces)); (3) D + derivation reduplication; (4) (D + derivation reduplication) + inflectional affix (formal or informal).